Comparisons of outcomes between ProKnife injection endoscopic submucosal dissection and conventional endoscopic submucosal dissection for large gastric lesions in ex vivo porcine model study: A randomized controlled trial - Mitsuru Esaki; Eikichi Ihara; Misato Esaki; Kei Nishioka; Yusuke Kimura; Yoshitaka Hata; Hirotaka Tsuru; Masafumi Wada; Yosuke Minoda; Xiaopeng Bai; Yoshihisa Shoguchi; Takayuki Nasu; et al. (DEN Open, 2022)
Abstract Objective To compare treatment outcomes between injection endoscopic submucosal dissection using ProKnife (P‐ESD) and conventional ESD (C‐ESD) for gastric lesions. Methods In this randomized controlled trial, we compared treatment outcomes of P‐ESD and C‐ESD for simulated gastric lesions ≥3 cm in resected porcine stomachs. Predictive factors associated with ESD difficulties were investigated using logistic regression analysis. Results Seventy lesions were screened; however, two lesions were excluded. A total of 12 endoscopists performed 68 ESDs: 34 P‐ESDs and 34 C‐ESDs. The ESD procedure time of P‐ESD (36.3 [28.4–46.8] min) was significantly shorter than that of C‐ESD (46 [36.4–64.6] min; p = 0.0014). The technical success rates did not differ between the P‐ESD and C‐ESD groups (en bloc resection rate, 100% in both groups; complete resection rate, 94.1% and 85.3%, respectively; p = 0.23). The number of injections during P‐ESD (7.5 [6–10] times) was significantly higher than during C‐ESD (4 [3–5] times; p < 0.001), but the total volume of injected solution during P‐ESD (20 [16–26.3] ml) was significantly smaller than during C‐ESD (27.5 [20–31.5] ml; p = 0.0019). In multivariate analysis, less ESD experience (odds ratio [OR], 3.9) and selection of C‐ESD as the ESD method (OR, 3.8) were independent predictive factors associated with ESD difficulties. Conclusions Compared with C‐ESD, P‐ESD had a shorter procedure time but also allowed for notable technical success and safety.